Assessment of “Non-Surgical Periodontal Therapy” on “Chronic Renal Disease” Patients - A Systematic Review Protocol - Baliga, Vidya; Baliga, Sudhindra; Oza, Ranu; Sharma, Varsha; Khatib, Mahalaqua Nazli (International Journal of Psychosocial Rehabilitation, 2020)
Background: Periodontal diseases are recognized as one of the risk factor responsible for various systemic diseases like insulin dependent or non-insulin dependent diabetes, cardiovascular abnormalities, pulmonary disorders, and chronic renal diseases (CRD). Arguably, subjects diagnosed with end-stage renal failure (ESRF) and the individuals receiving haemodialysis are more prone to periodontal tissue destruction and other deteriorating oral health related consequences. A higher “gingival index” and “bleeding on probing”, increased “pocket depths”, and greater “attachment loss” has been reported in patients with chronic renal failure (CRF). This could possibly be due to higher plaque indices reported in the dialysis and predialysis groups. In addition, more rapid calculus formation seen in dialysis patients than the systemically healthy individuals may be seen due to high salivary “urea” and “phosphate” levels. An improvement in the glomerular filtration rate has been observed after non-surgical periodontal therapy (NSPT) due to a decrease in the levels of inflammatory mediators that results in improving the periodontal status. Objectives: To evaluate the efficiency of NSPT in improving the periodontal health parameters, and thereby its effect on the renal parameters in patients suffering from CRD. Search Methods: We will search PUBMED without language restrictions up to NOVEMBER 2018. We will also search for ongoing studies in trial registers, perform handsearching, and check bibliographic references of relevant articles to seek potentially relevant research. We won’t apply any restrictions on language, date, or publication status. Selection Criteria: For execution of the review we are planning to include “randomized controlled trials” with parallelgroup or cross-over designs. Participants in the review will be adults aged 18 years and above with CRD and chronic periodontitis. COLLECTION OF DATA AND ITS ANALYSIS: Each individual study will independently be assessed by three review authors for its eligibility. Data extraction will then be executed by three review authors and will further be assessed for the “risk of bias” for each study independently using standard “Cochrane methodology”. We will assess the evidences using “GRADE” and will create a table for “Summary of findings”.